Methamphetamine-Induced Cardiomyopathy (MACM) in a Middle-Aged Man; a Case Report - Zulfiqar Qutrio Baloch; Muhammad Hussain; Shabber Agha Abbas; Jorge L. Perez; Muhammad Ayyaz (Emergency, 2017)
The development of methamphetamine-associated cardiomyopathy (MACM) represents a severe complication of chronic methamphetamine abuse. MACM-induced irreversible structural and functional changes in the heart can eventually lead to decompensated heart failure, ultimately requiring heart transplantation. In this case report we present a 47-year old male with a previous history of chronic amphetamine abuse who presented to the emergency room with severe dyspnea at rest associated with mild substernal non-radiating chest pain. He denied any previous cardiac history but had a positive urinary toxicology for methamphetamine. A complete cardiac workup ruled out all other etiologies. The patient required a 3-week intensive pharmacotherapy intervention to stabilize acute heart failure symptoms. At discharge he was classified as having New York Association Class III (NYHA-III) heart failure. His medical symptoms did not improve and he was considered for heart transplantation. With the increase in availability and abuse of methamphetamine, case of MACM such as ours are more frequently being encountered in the emergency departments. In addition to raising awareness, our case provides an outline of how MACM patients likely may present and the subsequent morbid sequela. Clinicians should maintain a high degree of suspicion when assessing all patients with a history of methamphetamine abuse. Early cardiac evaluation can help identify ventricular compromise in asymptomatic patients providing an opportunity to intervene prior to the development of irreversible MACM.